Clinical Presentation of Varicose Vein - A Hospital-based Cross-sectional Study - Santosh Shah; Raj Kumar KC; Rajesh Poudel; Santosh Mishra; Sagun Thapa; Sabir Miya; Pratik Adhikari (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTION Varicose veins are one of the major problems with patients presenting with symptoms of heaviness, tingling sensation, swelling, aching, restless legs, cramps and itching. Other clinical conditions with which patients presents are pigmentation of lower limbs, healed or active venous ulcers, lipodermatosclerosis. We studied various clinical presentations of varicose veins. MATERIAL AND METHODS A cross-sectional observational study was done in all patients presented to UCMS Teaching Hospital from 2021 to 2022.The primary objective was to assess various clinical signs and symptoms of patients with varicose veins. RESULTS Out of 260 patients, 172 were males and 88 were females. The mean age was 43.87±14.31 years. Patients with occupation involving long standing had more incidence of varicose veins with heaviness and aching as the most common clinical presenta- tion. CONCLUSION Security guard, cook, housewife, teacher, farmer occupational people seem to be affected. Heaviness and aching are more common symptoms, least common clinical presentation were bleeding, thrombosis, and ulceration.